2018
DOI: 10.1017/s0950268818002194
|View full text |Cite
|
Sign up to set email alerts
|

Association between Toxoplasma gondii exposure and paediatrics haematological malignancies: a case–control study

Abstract: The possible association between Toxoplasma gondii infection and paediatric haematological malignancies in a group of patients and control subjects was evaluated in the present study. We performed an age-, gender- and residence frequency-matched case-control study of 101 blood cancer patients under 18 years of age, all of which were treated in Amirkola Pediatric Hospital. One hundred and thirty-eight control samples were gathered from the outpatient clinic in the hospital. All cases and controls were tested fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
1
7
1
5
Order By: Relevance
“…Several studies demonstrate a latent relationship between toxoplasmosis and malignancy, including with brain and oral cancers [ 7 9 ]. In recent studies, patients with hematologic malignancies had higher seroprevalence of T. gondii antibodies [ 10 , 11 ]. Moreover, in Iran, T .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrate a latent relationship between toxoplasmosis and malignancy, including with brain and oral cancers [ 7 9 ]. In recent studies, patients with hematologic malignancies had higher seroprevalence of T. gondii antibodies [ 10 , 11 ]. Moreover, in Iran, T .…”
Section: Introductionmentioning
confidence: 99%
“…In Iran (553) out of (1,244) cancer patients was IgG seropositive to toxoplasmosis. In Iran the most common cancer type is leukaemia, and according to resent studies about 661 / million children under 14 years old are diagnosed with leukaemia, this can explain that the mortality rates associated with the sero-positive of toxoplasmosis [30]. In southwest of Iran most investigation according to several studies concluded that the children with malignance cancer diagnosed with high prevalence of acute and chronic toxoplasmosis and they requires special attention [17].…”
Section: Prevalence Of Toxoplasmosis In Cancer Patients (Iran)mentioning
confidence: 99%
“…En condiciones inmunológicas normales, la infección por T. gondii es usualmente asintomática y autolimitada 4 , pese a que se ha descrito su asociación con el desarrollo de diversas enfermedades tales como cirrosis hepática, epilepsia, esquizofrenia 4,5 e incluso leucemia en niños 4 .…”
Section: Introductionunclassified
“…Los pacientes con cáncer son un grupo considerable de hospederos inmunocomprometidos, tomando en cuenta que cada año se diagnostican cerca de 300.000 casos de cáncer en personas bajo 19 años en el mundo 4 . La neoplasia más frecuente es la hematológica, que representa cerca de 45% del total de nuevos diagnósticos pediátricos.…”
Section: Introductionunclassified
See 1 more Smart Citation